The relation between parent-reported fine motor skills and spelling performance in different test modes - Rothe, Josefine; Schulte-Körne, Gerd; Hasselhorn, Marcus; Visser, Linda (Frontiers in Education, 2025)
BackgroundChildren are using digital devices earlier and more frequently than they did years ago. At the same time fine motor skills and the spelling performance of primary school children have deteriorated over the last years. There is some evidence for a relationship between fine motor skills and spelling performance, while the role of test mode in this context is still unknown. Therefore, the aim of the present study was to evaluate the relation between parent-reported fine motor skills and spelling performance in different test modes.MethodsThe spelling performance of German children in 3rd and 4th grade (age: 8–12 years) was examined, first in digital test mode (N = 3,453; 49.1% girls) and then in paper-pencil mode (N = 225; 44% girls). Fine motor skills were assessed using a parental questionnaire.ResultsThe results confirm earlier findings of a positive relation between spelling performance and fine motor skills and reveal that using digital test mode leads to neither an immediate improvement nor a deterioration in spelling performance in children with low fine motor skills. Below-average fine motor skills appeared to have a more adverse effect on spelling performance in girls than in boys. Also, fine motor skills had an influence on school grade in German over and above its influence on reading and spelling abilities.ConclusionSwitching from paper-pencil to digital testing does not seem to bring immediate improvement for children with low fine motor skills, but is not a disadvantage either.